1994
DOI: 10.3109/02770909409044811
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Wheezing as the Cause of School Absence

Abstract: A survey was conducted on children attending 30 primary schools (15 each for boys ad girls) in Al-Ain City of United Arab Emirates (UAE) to assess the impact of asthma on school absenteeism. There are 28,447 primary school children (50% boys and 50% girls) aged 6-14 years in the Al-Ain Educational District, all of whose school health records were investigated with respect to school absence caused by asthma during the academic year 1991-1992. Results showed that overall 1910 (6.7%) pupils were diagnosed as havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
3
34
0
1
Order By: Relevance
“…(Figure 2) These results support the fact that air pollution has an impact on asthma. This is in agreement with other studies of two populations of Australian (Peat et al, 1987) and United Arab Emirates (Bener et al, 1994b) that high prevalence of asthma was found in primary school children during spring/summer seasons which led to more absenteeism from school. Air pollution has been associated with a number of detrimental health effects for children especially respiratory diseases.…”
Section: Asthma and Air Pollutionsupporting
confidence: 82%
See 2 more Smart Citations
“…(Figure 2) These results support the fact that air pollution has an impact on asthma. This is in agreement with other studies of two populations of Australian (Peat et al, 1987) and United Arab Emirates (Bener et al, 1994b) that high prevalence of asthma was found in primary school children during spring/summer seasons which led to more absenteeism from school. Air pollution has been associated with a number of detrimental health effects for children especially respiratory diseases.…”
Section: Asthma and Air Pollutionsupporting
confidence: 82%
“…In Qatar, 50.3% of the absenteeism was observed in asthmatic children studying in intermediate level (aged 12 -14 years). In the United Arab Emirates, 57% of asthmatic children aged 6-9 years missed at least 1 day of school compared with 42% in 10-14 year old similar children (Bener et al, 1994b). It is possible that increased absenteeism in younger asthmatic children due to the fact that asthma exacerbations are more severe in younger children.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Childhood respiratory problems of the sort that might be induced by air pollutants have also been associated directly and indirectly with lower academic performance (Fowler, Davenport, and Garg 1992;Bener, et al, 1994). In some communities, parents have complained of diminished school performance among their children due to health effects associated with outdoor and other pollution (Diette et al, 2000;Perera et al, 1999;Kaplan and Morris 2000).…”
mentioning
confidence: 99%
“…Equally important, the prevalence of asthma in Kuwait was higher than * p < 0.001. n = Number of students. that reported from UAE (6-7%) and Saudi Arabia (10.3%) [19] . Although the present study was conducted on bedroom dust, apparently the most important room in the house, only 2.7 and 3.5% of the houses had extremely low ( !…”
Section: Discussionmentioning
confidence: 69%